E-148 Decompressive craniectomy in acute stroke patients in korean single center. (22nd July 2019) - Jang, K; Cho, B; Moon, B; Kim, K; Jang, D
Abstract : Introduction: Decompressive craniectomy (DC) is a life-saving surgical procedure being increasingly employed for malignant intracerebral artery stroke. The purpose of this study is to investigate the characteristics and prognostic factors of patients undergoing DC after acute ischemic stroke. Method: From 2013 to 2018, we analyzed the prospective gathered data of 58 consecutive patients treated with DC after acute ischemic stroke in a single center. Also, we analyzed the prospective gathered data of 160 consecutive patients treated with mechanical thrombectomy using stent-retrievers for acute ischemic stroke in a single center. Demographic, clinical, laboratory, and radiologic features of each patient were investigated. We compared the characteristics of patients who underwent DC with those of patients who received medical treatment. Results: Of the total 3884 acute ischemic stroke patients, 58 patients(1.49%) were underwent DC. Of 289 patients who underwent mechanical thrombectomy due to acute ischemic stroke, DC was performed in 32 patients(11.07%). Of the patients who underwent mechanical thrombectomy due to acute ischemic stroke, post thrombectomy complications (100% vs 22.81%, p=0.000), preprocedural TICI grade (p=0.001) were significantly higher in patients who underwent DC compared to patients who did not receive craniectomy. 30 days mRS scores(5.13 vs 3.37, p=0.000), 90 days mRS scores(5.06 vs 3.17, p=0.000), ICU hospital days(21.53 vs 8.65, p=0.000) and hospital mortality(46.88% vs 12.5%, p=0.000) were significantly higher in the craniectomy patients. Conclusions: Patients who underwent DC had more post procedural complications, and the functional outcomes were worse after DC in acute ischemic stroke. However, since DC is the last treatment option for patients with severe cerebral infarction who are not responding to medical treatment, it is advisable to consider active management while managing the underlying disease and periprocedural complications. Disclosures: K. Jang: None. B. Cho: None. B. Moon: None. K. Kim: None. D. Jang: None.